2019
DOI: 10.1080/21691401.2019.1647222
|View full text |Cite
|
Sign up to set email alerts
|

MiR-638 suppresses the progression of oral squamous cell carcinoma through wnt/β-catenin pathway by targeting phospholipase D1

Abstract: View related articles View Crossmark data Citing articles: 5 View citing articles MiR-638 suppresses the progression of oral squamous cell carcinoma through wnt/b-catenin pathway by targeting phospholipase D1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Similarly deregulation of miR-572 and upregulation of miR-638 was exclusively associated with MM 16,48 . In contrast, downregulated expression of miR-638 was observed in our datasets as reported in other cancers including breast cancers 49 and oral squamous cell carcinoma 50 .…”
Section: Discussionsupporting
confidence: 55%
“…Similarly deregulation of miR-572 and upregulation of miR-638 was exclusively associated with MM 16,48 . In contrast, downregulated expression of miR-638 was observed in our datasets as reported in other cancers including breast cancers 49 and oral squamous cell carcinoma 50 .…”
Section: Discussionsupporting
confidence: 55%
“…Some studies have suggested that miR-638 and miR-182 may also target PLD1. 32,33 However, no changes in miR-638 were found in our microRNA microarray assay after cadmium exposure for 6 weeks.…”
Section: Discussionmentioning
confidence: 68%
“…Among these, miR‐638 is reported to function as a tumor suppressor and inhibits cell migration in HCC 33 . It also influences cancer cell progression through the Wnt/β‐catenin pathway and affects the cell cycle by suppressing cyclin D1 expression 34,35 . Another candidate, miR‐663a, also has a tumor suppressor function, showing anti‐proliferative effects and suppression of invasiveness and tumor growth in HCC 36 .…”
Section: Discussionmentioning
confidence: 99%
“…13 33 It also influences cancer cell progression through the Wnt/β-catenin pathway and affects the cell cycle by suppressing cyclin D1 expression. 34,35 Another candidate, miR-663a, also has a tumor suppressor function, showing anti-proliferative effects and suppression of invasiveness and tumor growth in HCC. 36 Conversely, miR-3648 is reported to promote cell invasion and migration in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%